2021
DOI: 10.1186/s13020-021-00454-x
|View full text |Cite
|
Sign up to set email alerts
|

The three syndromes and six Chinese patent medicine study during the recovery phase of COVID-19

Abstract: The coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), first broke out in Wuhan, China, in 2019. SARS-CoV-2 develops many types of mutations (such as B.1.1.7), making diagnosis and treatment challenging. Although we now have a preliminary understanding of COVID-19, including pathological changes, clinical manifestations, and treatment measures, we also face new difficulties. The biggest problem is that most COVID-19 patients might face sequelae (e.g., f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 105 publications
(108 reference statements)
1
16
0
Order By: Relevance
“…The result of a recent study that focused on sleep and mood disorders caused by the COVID-19 also supported our findings, and this study reported that SMC significantly improved depression and anxiety of patients with COVID-19 during the recovery phase. 43 Also, the findings were consistent with a variety of previous clinical studies. 44–47 The mechanism of mood symptoms improvements might be related to the Semen Ziziphi Spinosae, Radix Bupleuri, and Bombyx Batryticatus.…”
Section: Discussionsupporting
confidence: 89%
“…The result of a recent study that focused on sleep and mood disorders caused by the COVID-19 also supported our findings, and this study reported that SMC significantly improved depression and anxiety of patients with COVID-19 during the recovery phase. 43 Also, the findings were consistent with a variety of previous clinical studies. 44–47 The mechanism of mood symptoms improvements might be related to the Semen Ziziphi Spinosae, Radix Bupleuri, and Bombyx Batryticatus.…”
Section: Discussionsupporting
confidence: 89%
“…[ 38 ] Many of these herbal medicines are not only used throughout but are especially important in the recovery period. [ 19 , 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…An observational study of 420 convalescent COVID-19 patients showed that the recurrence rate of positive reverse transcriptase polymerase chain reaction (RT-PCR) tests in the comprehensive intervention group of TCM was significantly lower than that in the non-intervention group [ 5 ]. Through the clinical study of “the three syndromes and six Chinese patent medicine” during the recovery phase of COVID-19, it was found that Chinese patent medicines such as Jinshuibao Capsule, Shengmai Yin, Ludangshen Oral Liquid, Xiangsha Liujun Pill, and Shumian Capsule can improve cardiopulmonary dysfunction, digestive dysfunction, and sleep and emotional dysfunction of convalescent patients [ 6 , 7 ]. In addition, our clinical study also showed that Qimai Feiluoping Decoction could significantly promote the absorption of interstitial inflammation and pulmonary fibrosis in patients with severe/critical disease in the convalescent stage, and preliminarily explored its antifibrosis mechanism from the pharmacological level [ 8 ].…”
Section: Application Of Tcm In Fighting Epidemic Situationmentioning
confidence: 99%